Multiple brain metastases: resection with IORT versus adjuvant radiotherapy and concurrent irradiation of unresected lesions - Wieger, Gero; Godó Jiménez, Àlex; Brehmer, Stefanie; Etminan, Nima; Stieler, Florian; Giordano, Frank Anton; Ruder, Arne Mathias (Radiation oncology, 2025)
Treatment of multiple brain metastases (BM) often involves surgical resection of one lesion combined with stereotactic radiotherapy (SRT) to the resection cavity and unresected BM. Intraoperative radiotherapy (IORT) is an emerging alternative for treating the resection cavity, potentially dosimetric benefits. This study aimed to compare the dosimetry of treating the resection cavity with IORT versus adjuvant SRT when combined with SRT for additional unresected BM.
Gesehen am 16.12.2025